PREFERENCES EXPRESSED BY STUDENTS OF NINTH STANDARD TO THE ADOPTION OF VARIED SITUATIONS IN SITUATIONAL APPROACH - Ravi; Chinnappan, K. (International Journal of Research -GRANTHAALAYAH, 2017)
The present study is aimed at assessing the preferences of ninth standard students in various situations of situational approach of English language teaching. All the ninth standard students studying in the high and higher secondary schools in Thanjavur district form the population of the study. 200 ninth standard students have chosen randomly to form the sample of the study. Percentage analysis was the only statistical technique adopted to compute the number of students preferring each situation. A rating scale for student’s preference towards different situations was prepared and validated by the researcher to collect data. The percentage analysis of the collected data reveals that real life situations are the most preferred situation from the situational approach by ninth standard students; whereas verbal situation is the least preferred by them. Male students, Students from rural area, Students from government and aided schools have more preference towards real life situations; whereas female students, Students from urban area, Students from private schools shown preference towards classroom situations. Without any difference, all the category of students prefers verbal situations as the least effective situations of situational approach of teaching learning process. These findings may be handy in making aware of teachers to use various situations to teach language in the classrooms.